The Equal Marriage from the Logics of Private Internacional Law - Espiniella Menéndez, Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Recent cases have shown a renewed interest about the regulation of cross-border equal marriages, which can be analyzed from the logics that informs Private International Law. From a logic of International Law, equal marriage will be analyzed in light of human rights, the European integration process and the impact on the constitutional systems of States. As conclusion, it will be necessary to attenuate the public order of the States contrary to this marriage. From a logic of Private Law, the men-tioned attenuation of public policy is a particularly useful technique for the validity and effectiveness of cross-border equal marriage, issues of legal separation, divorce and property regime, as well as identity, nationality and maintenance and inheritance rights of the spouse of the same sex or gender.
Keywords: Equal marriage; ECHR; CJEU; separation; legal divorce; marriage annulment; same-sex spouse; nationality and identity; maintenance and inheritance rights